Real-life use of talimogene laherparepvec (T-VEC) in melanoma patients in centers in Austria, Switzerland and Germany - Erika Richtig (BMJ Publishing Group, 2021)
Background Talimogene laherparepvec (T-VEC) is a licensed therapy for use in melanoma patients of stage IIIB-IVM1a with injectable, unresectable metastatic lesions in Europe. Approval was based on the Oncovex Pivotal Trial in Melanoma study, which also included patients with distant metastases and demonstrated an overall response rate (ORR) of 40.5% and a complete response (CR) rate of 16.6%.Objectives The aim of this study was to assess the outcome of melanoma patients treated with T-VEC in a real-life clinical setting.Methods Based on data from 10 melanoma centers in Austria, Switzerland and southern Germany, we conducted a retrospective chart review, which included 88 patients (44 male, 44 female) with a median age of 72 years (range 36–95 years) treated with T-VEC during the period from May 2016 to January 2020.Results 88 patients fulfilled the inclusion criteria for analysis. The ORR was 63.7%. 38 patients (43.2%) showed a CR, 18 (20.5%) had a partial response, 8 (9.1%) had stable disease and 24 (27.3%) patients had a progressive disease. The median treatment period was 19 weeks (range: 1–65), an average of 11 doses (range: 1–36) were applied. 39 (45.3%) patients developed adverse events, mostly mild, grade I (64.1%).Conclusion This real-life cohort treatment with T-VEC showed a high ORR and a large number of durable CRs.